The places of modernity in early Mexican American literature, 1848-1948 - Aranda, José F., 1961- (Postwestern horizons., 2022)
José F. Aranda Jr. demonstrates how the burdens of modernity become the dominant discursive logic for understanding why people of Mexican descent nonetheless wrote and invested in print culture without any guarantee of its social, cultural, or political efficacy.